Análise de qualidade da atenção secundária em saúde bucal: Um olhar para o diagnóstico do câncer bucal - Araújo, Zacchia Hayvolla Fernandes Marinho de (2019)
Oral cancer is a worldwide public health problem, which in Brazil has higher rates of incidence and mortality in white men in the fifth decade of life. Early diagnosis and treatment are essential conditions to reduce its occurrence and contribute to a more favorable prognosis. Given the relevance of this condition, since 2004, with the implementation of the National Oral Health Policy, the Dental Specialty Center (CEO) is the main health service responsible for performing oral diagnosis, monitoring of suspected cases and referral for treatment and rehabilitation. Therefore, the objective of this study was to characterize the production of biopsies and their relationships with structural and work process aspects in the attention to oral cancer in the Dentistry Specialties Centers (CEO) of Brazil. For this, a cross-sectional, descriptive and analytical research was carried out, using two secondary databases, the first cycle of the Program for Improving Access and Quality of Dental Specialties Centers (PMAQ-CEO) and the Department of Information Technology of SUS (SIA / SUS). A total of 13 questions were used, including ten questions from "Module II - Interview with CEO and / or CEO Surgeon-Dentist" and three from "Module I - CEO Observation." Data were also used for HDI, GDP and municipal GINI. In the statistical analysis of the information collected, the Chi-Square test was used to verify the associations between the independent and dependent variables. Subsequently, the strength and the association effect between these variables were evaluated using the "OddsRatio" Chances Ratio, calculated using the binary logistic regression model. The results revealed that only 43.0% of the CEOs recorded biopsy production in 2013 and the Southeast and South regions produced 72.4% of the total biopsies. Soft tissue biopsy of the mouth was the most performed with 95.8% of the production. The CEO type II presented better performance in this production. Some structural factors and the internal work process of the CEO (CEO rank, cancer user registry, reference high complexity) seem to have a positive effect on biopsy production. The relationships found are used to plan oral cancer actions.